Lower Choline-Containing Metabolites/Creatine (Cr) Rise and Failure to Sustain NAA/Cr Levels in the Dorsolateral Prefrontal Cortex Are Associated with Depressive Episode Recurrence under Maintenance Therapy: A Proton Magnetic Resonance Spectroscopy Retrospective Cohort Study - Henigsberg, Neven; Šarac, Helena; Radoš, Marko; Radoš, Milan; Ozretić, David; Foro, Tamara; Erdeljić Turk, Viktorija; Hrabač, Pero; Bajs Janović, Maja; Rak, Benedict; Kalember, Petra (Frontiers in Psychiatry, 2017)
Background The aim of this study was to evaluate the relationship between changes in proton magnetic resonance spectroscopy (1H-MRS) parameters at the start of the index episode recovery phase and at recurrence in patients with recurrent depression who were treated with prolonged maintenance therapy. Methods 1H-MRS parameters were analyzed in 48 patients with recurrent depression who required maintenance therapy with antidepressant medication prescribed by a psychiatrist and who continued with the same antidepressant during the maintenance phase, either to recurrence of depression, completion of the 10-year observation period, or the start of the withdrawal phase (tapering-off antidepressant). N-acetylaspartate (NAA), choline-containing metabolites (Cho), creatine (Cr), and glutamine/glutamate were measured at the start of the recovery phase and 6 months later. Results Recurrent depressive episodes occurred in 20 patients. These individuals had a smaller increase in Cho/Cr after the beginning of the recovery phase compared to the non-recurrent patient group and also exhibited a decreased NAA/Cr ratio. Conclusion Sustainable NAA and increased Cho levels at the onset of the recovery phase of the index episode are early markers of antidepressant effectiveness associated with a lower risk of major depressive disorder recurrence. The NAA and Cho changes in the non-recurrent group may be attributable to increased brain resilience, contrary to the transient temporal effect observed in subjects who experienced a depressive episode.